There is an alternative : economic policies and labour strategies beyond the mainstream - Pons-Vignon, Nicolas (International Labour Office, 2011)
A key message of the 2011 Global Labour Column anthology is that we need a plurality of ideas in order to develop and ultimately choose between different policy options. This volume will be of great interest to academic scholars as well as trade union activists and policy-makers.